2019
DOI: 10.26452/ijrps.v10i4.1748
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioactivity of Pure ZnO and ZnO-Ag nanocomposite Using Sol-Gel method for Self-Cleaning Application

Abstract: In the current study, Pure ZnO and Ag-ZnO nanocomposite are established using the sol-gel method with the influence of ammonia solution NH4OH to incorporate Ag ions into ZnO and form Ag-ZnO nanocomposites. Then pure ZnO and Ag-ZnO nanocomposites were annealed at 450oC for tow h in a muffle furaning using temperture controlling, and heat rate was set at temperature 100oC per min. The structural and morphological properties of samples were characterized using XRD, FTIR, and FESEM with Energy dispersive X-rays (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Numbers of articles deals with antibacterial activity of different nanomaterials like Ag, Au, CuO, TiO2 and etc. which are improve the successful against different drug resistant bacteria, viral and fungal strains [6][7][8][9][10][11]. The nanomaterials field is focused on producing and using particles of nanometer size scale that can interact with microbial cell through a variety of mechanism as shown in biomedical and biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numbers of articles deals with antibacterial activity of different nanomaterials like Ag, Au, CuO, TiO2 and etc. which are improve the successful against different drug resistant bacteria, viral and fungal strains [6][7][8][9][10][11]. The nanomaterials field is focused on producing and using particles of nanometer size scale that can interact with microbial cell through a variety of mechanism as shown in biomedical and biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although the common chemical and physical approaches to synthesize the nanoparticle, it's found that the usage of toxic complexes bounds their uses. To overwhelm the toxicity trouble in formation, harmless friendly green approaches possess a chief role for resulting nanoparticles [10,11]. Several authors have documented such green fabricated strategy for the homogeneous and monodisperse nanoparticles manufacturing utilizing starch as capping agent.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have documented such green fabricated strategy for the homogeneous and monodisperse nanoparticles manufacturing utilizing starch as capping agent. In the green fabricated approach, it's significant to utilize the nontoxic chemicals, environmentally being solvents, and renewable materials [10][11][12]. Polysaccharides are natural and renewable polymers which represented environmentally safe source with low toxic effect.…”
Section: Introductionmentioning
confidence: 99%